Obstructive Sleep Apnea, Oxidative Stress, and Cardiovascular Disease: Evidence from Human Studies. (8th June 2015) - Eisele, Hans-Joachim; Markart, Philipp; Schulz, Richard
Abstract : Obstructive sleep apnea (OSA) is a frequent disease mainly affecting obese people and caused by repetitive collapse of the upper airways during sleep. The increased morbidity and mortality of OSA are mainly thought to be the consequence of its adverse effects on cardiovascular (CV) health. In this context, oxidative stress induced by nocturnal intermittent hypoxia has been identified to play a major role. This is suggested by biomarker studies in OSA patients showing excessively generated reactive oxygen species from leukocytes, reduced plasma levels of nitrite and nitrate, increased lipid peroxidation, and reduced antioxidant capacity. Biopsy studies complement these findings by demonstrating reduced endothelial nitric oxide synthase expression and increased nitrotyrosine immunofluorescence in the vasculature of these patients. Furthermore, oxidative stress in OSA correlates with surrogate markers of CV disease such as endothelial function, intima-media thickness, and high blood pressure. Continuous positive airway pressure therapy reverses oxidative stress in OSA. The same may be true for antioxidants; however, more studies are needed to clarify this issue.